A 5.9 GHz Low Power and Wide Tuning Range CMOS Current-controlled Ring Oscillator - Prapto Nugroho; Ramesh K. Pokharel; Haruichi Kanaya; Keiji Yoshida (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Designing low power, low noise, wide tuning range and small size circuit in one single chip is very challenging. This paper describe a low power, wide tuning range three-stage current-controlled ring oscillator (CCO) designed on 0.18um CMOS technology. The CCO circuit has tuning range from 251 MHz to 5.5 GHz or 183% wide. It consumes only 144 uA to 9.76mA by using 1.8V power supply. Phase noise is -104 dBc /Hz at 5.5 GHz and 4 Mhz offset frequency.  Calculated FoM is -154.4 dBc /Hz which is the best among published counterpart papers. The size of the core oscillator circuits without bonding pads is only 0.0003 mm2.DOI:http://dx.doi.org/10.11591/ijece.v2i3.229